2000
DOI: 10.1248/bpb.23.962
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-Inducing Activity of Lupeol, a Lupane-Type Triterpene from Chinese Dandelion Root (Hokouei-kon), on a Mouse Melanoma Cell Line.

Abstract: We examined the differentiation-inducing effects of extracts of 49 wild plants, 25 types of seaweed and 26 mushrooms in Akita on the human leukemia cell line HL60 and a B16 mouse melanoma-derived sub-clone with high differentiation capability (B16 2F2). Differentiation inducers of HL60 cells such as retinoic acid, showed no effects on the differentiation of B16 2F2 cells. Furthermore, chemical compounds known to be inducers of B16 cells, did not induce differentiation of HL60 cells. Screening tests showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 1 publication
0
28
0
Order By: Relevance
“…The activity of B16 2F2 cells was detected widely in Compositae plants, brown algae and some mushrooms such as Tricholoma sp. (Hata et al 2000). By bioassay-guided fractionation, we isolated 4 lupane triterpenes (compounds 1-4, Fig.…”
Section: Isolation Of Melanogens From Compositae Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of B16 2F2 cells was detected widely in Compositae plants, brown algae and some mushrooms such as Tricholoma sp. (Hata et al 2000). By bioassay-guided fractionation, we isolated 4 lupane triterpenes (compounds 1-4, Fig.…”
Section: Isolation Of Melanogens From Compositae Plantsmentioning
confidence: 99%
“…By bioassay-guided fractionation, we isolated 4 lupane triterpenes (compounds 1-4, Fig. 1) as melanogens from two Compositae plants, Chinese dandelion root and Lactuca indica (Hata et al 2000;Hata et al 2003a). The cell growth and melanin contents after treatment with compound 1 (= lupeol) at various concentrations for 72 h are shown in Fig.…”
Section: Isolation Of Melanogens From Compositae Plantsmentioning
confidence: 99%
“…Much research has concentrated on different plant extracts' abilities to induce apoptosis of cancer cells. [3][4][5] Overwhelming evidence indicates the involvement of caspases in apoptosis. Caspases make up of a family of cysteine proteases that cleave substrates after aspartic residue.…”
mentioning
confidence: 99%
“…Several previous studies indicated that lupeol exhibits antitumor activities against melanoma cells in vitro (9,(11)(12)(13)(14)(15)(16). A previous study by Saleem et al (11) demonstrated that intraperitoneal injection of lupeol inhibits tumor growth in a human Table I.…”
Section: Discussionmentioning
confidence: 99%